PENERAPAN PROJECT BASED LEARNING UNTUK MENUMBUHKAN JIWA KEWIRAUSAHAAN DAN HASIL BELAJAR SISWA SMA KELAS XII IPA PADA MATERI RESPIRASI ANAEROB DI SMA NEGERI 3 PONTIANAK - RINI ASTUTI, S.Si., M.Pd (JARDIKNAS - Jurnal Pendidikan dan Sosial, 2021)
The objectives of this Classroom Action Research are 1) To describe the implementation of Project Based Learning for Class XII IPA high school students on anaerobic respiration materil, 2) To describe the growing entrepreneurial spirit of Class XII IPA high school student in anaerobic respiration material, 3) To describe the improvement of student learning outcomes Class XII IPA high scholl student on anaerobic respiration material. This classroom action research was conducted in Class XII IPA 4 for the 2019/2020 school year at SMA Negeri 3 Pontianak. The subjects of the perpetrators of the action were 1 (one) Biology teacher, the subjects receiving the action were 37 students of class XII IPA 4. The data sources of this study were written document and sources. Written document in the form of a list of grades, teaching journals, and student projects. The research data were collected using techniques (a) tests, (b) observation, (c) questionnaires, (d) study documentation, and (e) field notes. The research process was carried out in two cycles, each of which consisted of 4 stages, namely : (1) action planing, (2) action implementation, (3) observation, (4) and action reflection. The results of study indicate that the application of project based learning with a survey apprach can the learning outcomes of students in Class XII IPA 4 at SMA Negeri 3 Pontianak, and the growth of an entrepreneurial spirit. The results obtained before the application of project based learning with a survey approach were the average score of learning outcomes in Biology 75,12 and the results obtained after the application of project based learning with a survey approach were the average score of learning outcomes in Biology, namely 82,22. The completeness of learning in the first cycle is 51,85% complete, then in the second cycle it is 100% complete. Entrepreneurial spirit is indicated by the average product selling value of 84,33 in the high category. It is suggested that can optimize project based learning with a variety of different approaches.